The Role of Prosecutors in Paying Compensation to Customers Through Substitute Money for Corruption Crimes in BPR Salatiga in the Perspective of Progressive Justice - Nana Rosita Sari; Sulistyanta (MultiTech Publisher, 2023)
The role of prosecutors in the law enforcement system for corruption is not enough just to impose prison sanctions but also to make efforts to recover state losses caused. The role of the prosecutor is to spearhead efforts to recover or recover state financial losses. The case of the corruption case of PD BPR Salatiga with the Supreme Court Cassation Decision Number: 5969 K / Pid.Sus / 2022 dated November 9, 2022 on behalf of the convicted Sunarti, the Prosecutor has confiscated assets against the property of the convicted Sunarti so that later it can reduce the nominal replacement money imposed on the convicted of corruption. But the problem in the case of PD BPR Salatiga corruption is that the money that has been corrupted by the convict who in fact is a former employee of PD BPR Salatiga is the money of PD BPR Salatiga customers so that whether the replacement money that has been paid or taken from assets that have been confiscated must be confiscated to the state or returned to PD BPR Salatiga or handed over to the aggrieved customer. The State is a representative of a society, when the community becomes a victim and is harmed, this is where the State must contribute to solving problems fairly and wisely.